Exploring the potential of microalgae for new biotechnology applications and beyond: A review. (September 2018) - Rizwan, Muhammad; Mujtaba, Ghulam; Memon, Sheraz Ahmed; Lee, Kisay; Rashid, Naim
Abstract: The potential of microalgae as an alternative energy source has been adequately studied. However, exclusive use of microalgae as an energy feedstocks cannot warrant their scalability and economical sustainability due to the high cost involved in their biomass processing. The co-processing of microalgae biomass with other related bio-refinery applications can offset their cost and improve their sustainability. Thus, it triggers up the need of exploring the potential of microalgae biomass beyond their typical use. Microalgae offer interesting features to qualify them as alternative feedstocks for various bio-refinery applications. Microalgae have unique abilities to utilize them for industrial and environmental applications. Thus, this review discusses to expand the scope of integrating microalgae with other biotechnological applications to enhance their sustainability. The use of microalgae as a feed for animal and aquaculture, fertilizers, medicine, cosmetic, environmental and other biotechnological applications is thoroughly reviewed. It also highlights the barriers, opportunities, developments, and prospects of extending the scope of microalgae. This study concludes that sustained research funding, and a shift of microalgae focus from biofuels production to bio-refinery co-products can qualify them as promising feedstocks. Moreover, technology integration is inevitable to off-set the cost of microalgae biomass processing. It is expected that this study would be helpful to determine the future role of microalgae in bio-refinery applications.